Factors influencing the self-management ability among older adults experiencing intrinsic capacity decline: a cross-sectional study - Liu, Qingcai; Li, Xiaoyang; Hu, Mingyue; Zhao, Yinan; Wu, Shuang; Feng, Hui (Frontiers in Aging Neuroscience, 2024)
AimsThis study investigated the current status of intrinsic capacity and self-management abilities and analyzed the factors influencing the self-management abilities of older adults experiencing intrinsic capacity decline.MethodsWe included a sample of 382 older adults, with an average age of 72.92 ± 6.81 years, exhibiting intrinsic capacity decline in 38 communities in China. Questionnaires were administered using the sociodemographic questionnaire, the intrinsic capacity questionnaire, the social support scale, the self-rated health item, the eHealth literacy scale, and the self-management ability scale. The data were analyzed using descriptive statistics, Pearson correlation coefficients, and linear regression analysis.ResultsIn this study, 43.5% of older people had impairments in three of the five dimensions of intrinsic capacity, the most significant proportion. The self-management ability score of older adults experiencing intrinsic capacity decline was 67.05 ± 12.53 out of 100. There were significant associations between age, perceived social support, and intrinsic ability composite score with self-management abilities (Age: β = −0.263; p < 0.001; social support: β = 0.291; p < 0.001; intrinsic capacity composite score: β = 0.179; p < 0.001). Higher levels of self-management ability were associated with more effective maintenance of psychological capacity, regardless of the type of older adults experiencing IC decline (all p < 0.05). For example, among older adults experiencing cognitive decline, maintaining psychological function was positively associated with self-management abilities (β = 0.294; p < 0.01).ConclusionThe highest prevalence of concurrent impairments across three dimensions of intrinsic capacity was observed among older adults experiencing diminished intrinsic capacity. Fostering self-management abilities through social support and mental health interventions may benefit people experiencing intrinsic capacity decline.